Airway compression management in late-presenting absent pulmonary valve syndrome. (2nd January 2014) - Martinez-Esteve Melnikova, Anastasia; Sologashvili, Tornike; Beghetti, Maurice; Tissot, Cécile; Kalangos, Afksendiyos; Corbelli, Regula; Aggoun, Yacine; Didier, Dominique; Myers, Patrick O.
Abstract Introduction: Patients with absent pulmonary valve syndrome often present early with airway compression from aneurysmal pulmonary arteries. This study reviews our experience in managing absent pulmonary valve syndrome in later presenting children, and techniques used for managing airway compression. Methods: This study is a retrospective chart review of all patients who underwent repair of absent pulmonary valve syndrome from 2000 to 2012 at our institution. The primary endpoints were post-operative bronchoscopic and clinical evidence of persistent airway compression and need for reinterventions on the pulmonary arteries. Results: A total of 19 patients were included during the study period. The mean age at repair was 4.1±3.0 years (range 10 months–11 years). In all, seven patients had pre-operative bronchoscopic evidence of airway compression, which was managed by pulmonary artery reduction plasty in four patients and Lecompte manoeuvre in three patients. There were no peri-operative deaths. In patients with pulmonary artery plasty, two had no post-operative airway compression, one patient had improved compression, and one patient had unchanged compression. In patients managed with a Lecompte manoeuvre, two patients had no or trivial airway compression and one had improved compression. There were six late reinterventions or reoperations on the pulmonary arteries – two out of four in the pulmonary artery plasty group and one out of three in the Lecompte group. Conclusions: Most late-presenting patients with absent pulmonary valve syndrome do not have airway compression. Either pulmonary artery reduction plasty or the Lecompte manoeuvre can relieve proximal airway compression, without a significantly different risk of pulmonary artery reintervention between techniques.